If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + -2) + 3(5t) = 30 Reorder the terms: 2(-2 + t) + 3(5t) = 30 (-2 * 2 + t * 2) + 3(5t) = 30 (-4 + 2t) + 3(5t) = 30 Remove parenthesis around (5t) -4 + 2t + 3 * 5t = 30 Multiply 3 * 5 -4 + 2t + 15t = 30 Combine like terms: 2t + 15t = 17t -4 + 17t = 30 Solving -4 + 17t = 30 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 17t = 30 + 4 Combine like terms: -4 + 4 = 0 0 + 17t = 30 + 4 17t = 30 + 4 Combine like terms: 30 + 4 = 34 17t = 34 Divide each side by '17'. t = 2 Simplifying t = 2
| x/20=8/32 | | 1.5/2.129= | | 10=60x/600 | | 34-x=-2 | | -4=-2x-1+1 | | (14x+1)-9x= | | (x-20)x=90 | | 9/10=3x/2-7x/5 | | 175-n=143 | | (x-20)+x=20 | | -3x-5y=45 | | 53-x=-1 | | 6y+5(y+2)=5y+8 | | (3x+25)2x=180 | | 3x+7y=-12 | | -n+10-2n=-5(n+2) | | 60x/600 | | 2=a-6+3a | | A=D-B-C | | 9x-3(2-x)=4(3x+8)-7x | | x^2=0.11-1.8x | | (6x+11+9x)= | | r+7-1=6 | | 0.7=x-1.2x | | b/5-9=-1 | | 9000=.07*1*x | | 43=-7+5x | | 3ln(3x-4x^3)=0 | | X+2y=195 | | x*y=24 | | 2.8=ln(y) | | 9000=.05*1*x |